2018
DOI: 10.1155/2018/3745651
|View full text |Cite
|
Sign up to set email alerts
|

Pain Reconceptualisation after Pain Neurophysiology Education in Adults with Chronic Low Back Pain: A Qualitative Study

Abstract: Pain neurophysiology education (PNE) is an educational intervention for patients with chronic pain. PNE purports to assist patients to reconceptualise their pain away from the biomedical model towards a more biopsychosocial understanding by explaining pain biology. This study aimed to explore the extent, and nature, of patients' reconceptualisation of their chronic low back pain (CLBP) following PNE. Eleven adults with CLBP underwent semistructured interviews before and three weeks after receiving PNE. Intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 38 publications
1
31
0
1
Order By: Relevance
“…It appeared that a biomedical focus was tenacious and that any shift in beliefs was vulnerable to being contradicted and undermined by other health professionals. This finding is supported by previous qualitative research following pain science education, where varying degrees of reconceptualization were observed, from zero to almost complete [ 56 ]. While face-to-face interviews may have increased the depth of the responses, and these results highlight the need for future quality improvement innovations in pain management to develop more effective and convincing ways of delivering this important message.…”
Section: Discussionsupporting
confidence: 86%
“…It appeared that a biomedical focus was tenacious and that any shift in beliefs was vulnerable to being contradicted and undermined by other health professionals. This finding is supported by previous qualitative research following pain science education, where varying degrees of reconceptualization were observed, from zero to almost complete [ 56 ]. While face-to-face interviews may have increased the depth of the responses, and these results highlight the need for future quality improvement innovations in pain management to develop more effective and convincing ways of delivering this important message.…”
Section: Discussionsupporting
confidence: 86%
“…However, participation in group sessions could also be experienced as negative, because of fear that their pain might be reinforced if they listened to other people's pain stories. King et al (King et al, 2018) found that patients with chronic LBP showed varying levels of reconceptualization (≈ changes in beliefs about back pain) 3 weeks after receiving one session of group education. The degree of reconceptualization was influenced by the patients' previous beliefs and the estimated relevance of the information, and was related to the perceived benefit, and patients without perceived benefit did not change their perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of reconceptualization was influenced by the patients' previous beliefs and the estimated relevance of the information, and was related to the perceived benefit, and patients without perceived benefit did not change their perceptions. King et al (King et al, 2018) suggest that having more sessions and combining the education with other interventions may improve the benefits. Translated into CSM terminology, group education may heighten the possibility for patients to reflect upon and influence illness and treatment beliefs, and content of personalized condition-specific action plans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like cognitive behavioural therapy, this technique aims to change patients' inappropriate beliefs and consequent behaviours (King, 2018). However, to properly guide patients in pain management, health professionals must themselves have a basic knowledge of pain neuroscience Nijs et al, 2013;Adillón et al, 2015;Alodaibi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%